(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This article analyses the depiction of women in the verbal text of a history textbook used at junior secondary school level in Malawi. The focus falls on how women are depicted in the textbook and why they are depicted the way they are. The article is based on empirical research and utilised a feminist theoretical perspective. The verbal text was analysed quantitatively using open coding. Based on the analysis we argue that women, as historical characters, are generally subordinated and oppressed in a number of ways. This includes under-representation, marginalisation and omission. Since what is written in textbooks is regarded as authoritative depictions like these can send a negative message to learners and teachers as users of the textbooks about women as historical characters. We also argue that our findings from the Malawi context resonate with similar research done globally which for the most part can be attributed to the patriarchal societies women find themselves in. To change this situation we recommended that the junior secondary history syllabus and textbooks be updated and aligned to the Malawian constitution and gender equality policies.